2019
DOI: 10.3389/fneur.2019.00473
|View full text |Cite
|
Sign up to set email alerts
|

Alice in Wonderland Syndrome as a Presenting Manifestation of Creutzfeldt-Jakob Disease

Abstract: Background: Alice in Wonderland syndrome (AIWS) is a rare neurological disorder characterized by distortions of visual perception (metamorphopsias), the body image, and the experience of time, along with derealization and depersonalization. Some 85% of patients present with perceptual distortions in a single sensory modality, e.g., only visual or only somesthetic in nature. Moreover, the majority experience only a single type of distortion, e.g., only micropsia or only macropsia. AIWS has many diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…Even if chronic cases have been reported (Cooper et al, 2012), akinetopsia seems a rather transient condition (Shipp et al, 1994), suggesting the existence of functionally neuroplastic changes able to establish alternative neural interactions to restore sensitivity to visual motion. Such a relative ease to naturally react to akinetopsia makes it difficult to detect, especially in populations characterized by high neural plasticity like children, where in fact akinetopsia is relatively rare and usually present in combination with the Alice in Wonderland syndrome as a results of encephalitis (Naarden et al, 2019).…”
Section: Akinetopsiamentioning
confidence: 99%
“…Even if chronic cases have been reported (Cooper et al, 2012), akinetopsia seems a rather transient condition (Shipp et al, 1994), suggesting the existence of functionally neuroplastic changes able to establish alternative neural interactions to restore sensitivity to visual motion. Such a relative ease to naturally react to akinetopsia makes it difficult to detect, especially in populations characterized by high neural plasticity like children, where in fact akinetopsia is relatively rare and usually present in combination with the Alice in Wonderland syndrome as a results of encephalitis (Naarden et al, 2019).…”
Section: Akinetopsiamentioning
confidence: 99%
“…Such clinical presentations may lead to differential diagnoses including AIWS. Similar care studies highlight complex clinical presentations including migrainous hallucinations [29] , Creutzfeldt-Jakob Disease [30] , paroxysmal nonepileptic events [31] , and other medical conditions. Similar scarcity of studies was found for therapeutic measures.…”
Section: Resultsmentioning
confidence: 90%
“… 2 , 4 , 11 Other visual presentations reported in literature include blurred vision, visual field restriction, disturbed color perception, cortical blindness, 11 and even “Alice in Wonderland” syndrome consisting of visual metamorphopsias. 12 There are reports of non-specifically altered vision associated with depressive symptoms but being mistaken for a primary psychiatric disease instead of sCJD. 13 …”
Section: Discussionmentioning
confidence: 99%
“…2,4,11 Other visual presentations reported in literature include blurred vision, visual field restriction, disturbed color perception, cortical blindness, 11 and even "Alice in Wonderland" syndrome consisting of visual metamorphopsias. 12 There are reports of non-specifically altered vision associated with depressive symptoms but being mistaken for a primary psychiatric disease instead of sCJD. 13 The pathognomonic MRI findings in the Heidenhain variant of sCJD are the DWI cortical ribboning appearances involving the occipital lobes; 14 temporal and parietal lobe involvement without basal ganglia signal change, as seen in our patient's neuro-imaging, have also been described.…”
Section: Discussionmentioning
confidence: 99%